EU policy towards the south caucasus - İskenderov, Anar (My University, 2009)
Bu çalışmanın amacı Avrupa Birliği’nin Güney Kafkasya bölgesi ile olan ilişkilerini incelemek ve bu çerçevede bölgeye yönelik hukuki, iktisadi, ve siyasi politikalarını değerlendirmektir. Bu bağlamda, tezde Avrupa Birliği’nin geliştirdiği politika araçları ele alınırken, Güney Kafkasya politikasının belirleyici unsurları ve bölgede uyguladığı dış politikanın etkinliği incelenmiştir. Tezin temel argümanı, hem AB’nin kendi politikaları, hem de bununla ilişkin dış politika araçlarının bölgeyle ilgili temel hedeflerine ulaşma konusunda yetersiz kaldığı yönündedir. Bu yetersizlik, AB’nin bölgeye yönelik olarak uyguladığı politik enstrumanların yetersizliğinden, üyelerin ulusal çıkarlarını korumak amacı ile AB politakalını uygulamadaki eksiklillerinden, bölgesel çatışmaların çözümüne ilişkin izlediği politikaların başarısızlığından, AB’nin amaçları ve stratejik araçlarında işbirliğinin yeterli düzeyde mevcut olmamasından kaynaklanıyor. Bu tez dört bölümden oluşmaktadır: ney Kafkas ülkelerinin jeopolitik önemi ve söz konusu ülkelerde bağımsızlık kazandıktan sonraki gelişmeleri kapsamaktadır. İkinci Bölüm AB’nin Güney Kafkasya politikasının gelişim tarihini ve belirleyici hukuki unsurlarını analiz etmektedir. Üçüncü bölümde AB ve Güney Kafkas ülkeleri arasındaki ekonomik ilişkiler ele alınmıştır. Son bölümde ise AB’nin bölgede uyguladığı siyaset ve etkinliği incelenmiş ve tez sonuçlandırılmıştır.

In this study political and economic relations between the European Union and South Caucasus countries and the legal framework of these relations were examined under the title of “European Union’s Policy towards the South Caucasus”. The aim of this study is to put forth the policies of European Union towards the South Caucasus countries and to analyze adequacy of relations with the countries of Azerbaijan, Armenia and Georgia forming region. The research argues that the EU’s current policy approach is not well-tailored to ensure its increasing interests since the EU is not capable to influence the South Caucasus states. Although the EU’s current approach to the region has its own logic, the study suggests that the irrelevance in this point could be linked to failure of the EU’s policies towards the resolution of regional conflicts, weaknesses concerning the EU’s objectives and its strategic instruments, dualistic nature of the EU foreign policy as well as lack of cooperation with international actors in appropriate level to realize EU goals. The thesis consists of four chapters: The First chapter explores South Caucasus’ geopolitical significance and the developments occurred in the region after gaining independence. The Second Chapter analyzes Partnership and Cooperation Agreements which is the basic legal script drawing the framework of relations. The third chapter examines the economic relations between Union and the South Caucasus states. The final chapter aims to analyze the political relations and the efficiency of the EU’s foreign policies initiated in the region and concludes the thesis.
Keywords: Avrupa Birliği; Uluslararası Siyaset